Desenvolvimento de Editores Colaborativos em Tempo Real: Revisão Rápida - Dantas, Laurentino Augusto; Silva, Joab Cavalcante da; Pimentel, Maria da Graça C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Currently, users expect to collaborate synchronously with others, including over the Web. Developing a real-time collaborative editor (RCE) that enables geographically dispersed users to simultaneously edit the same document relies on specific algorithms and techniques. To understand how real-time collaborative editors are developed and tested, and which algorithms or techniques are crucial for their development, we conducted a systematic review addressing the following questions: For which types of objects does the literature present real-time collaborative editing systems (RTCE)? What is the most commonly used architecture by researchers to implement RTCE systems, how are they represented, and which works present models or roadmaps for the development of RCEs? Between Operational Transformation (OT) and Conflict-free Replicated Data Types (CRDTs) algorithms, which one appears most frequently in the selected works? What are the main types of tests conducted to evaluate collaborative editors, which articles conducted user tests, and what is the average number of users involved in these tests? Which works discuss undo/redo techniques? Which works discuss the use of comments, chat, or history as tools to support collaborative work? After screening 365 records published between 1993 and 2024, the review analyzed 23 studies published between 2002 and 2022. The results revealed various approaches and techniques employed in the implementation of RTCEs, offering a comprehensive view of research in this area. This, in turn, allowed for the identification of challenges that future research should address.